THE ROLE OF THE MADRASAH PRINCIPAL IN DEVELOPING THE QURAN MEMORIZATION CURRICULUM - Kunta, Ittaqillah Haitsuma; Iqna’a, Faiq Julia; Yakin, Ainul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research examines the role of the headmaster in developing the Tahfidzul Qur'an curriculum at Madrasah Tsanawiyah Zainul HasanPajarakan Probolinggo. The study aims to analyze the leadership strategies, curriculum planning, and implementation to enhance students' ability to memorize the Qur'an. The findings highlight that the headmaster plays a crucial role in establishing a clear vision, motivating staff, and ensuring the curriculum is tailored to the needs of the students. The leadership strategies implemented include creating a conducive environment for Qur'an memorization, regular assessments, and active involvement of parents and the community. The curriculum planning emphasizes effective methods such as tasmi' (listening to students' recitations) and muraja'ah (revision), which are integrated into students' daily routines. The implementation of these strategies has shown a significant impact on students' ability to improve their Qur'an memorization consistently. The study concludes that the leadership of the headmaster is pivotal in ensuring the success of the Tahfidzul Qur'an curriculum, fostering a disciplined, spiritually enriched, and academically capable generation. The research recommends adopting similar strategies in other madrasahs to enhance the overall quality of Qur'an memorization programs.